Colistin Combined With Tigecycline: A Promising Alternative Strategy to Combat Escherichia coli Harboring blaNDM–5 and mcr-1 - Zhou, Yu-Feng; Liu, Ping; Zhang, Chuan-Jian; Liao, Xiao-Ping; Sun, Jian; Liu, Ya-Hong (Frontiers in Microbiology, 2020)
Infections due to carbapenem-resistant NDM-producing Escherichia coli represent a major therapeutic challenge, especially in situations of pre-existing colistin resistance. The aim of this study was to investigate combinatorial pharmacodynamics of colistin and tigecycline against E. coli harboring blaNDM-5 and mcr-1, with possible mechanisms explored as well. Colistin disrupted the bacterial outer-membrane and facilitated tigecycline uptake largely independent of mcr-1 expression, which allowed a potentiation of the tigecycline-colistin combination. A concentration-dependent decrease in colistin MIC and EC50 was observed with increasing tigecycline levels. Clinically relevant concentrations of colistin and tigecycline combination significantly decreased bacterial density of colistin-resistant E. coli by 3.9 to 6.1-log10 cfu/mL over 48 h at both inoculums of 106 and 108 cfu/mL, and were more active than each drug alone (P<0.01). Importantly, colistin and tigecycline combination therapy was efficacious in the murine thigh infection model at clinically relevant doses, resulting in >2.0-log10cfu/thigh reduction in bacterial density compared to each monotherapy. These data suggest that the use of colistin and tigecycline combination can provide a therapeutic alternative for infection caused by multidrug-resistant E. coli that harbored both blaNDM-5 and mcr-1.